Development of Elementary School Learning Based on Flash 8 Animation - A Wathon (Mentari : Journal of Islamic Primary School, 2025)
The use of technology in education has now become a necessity, especially in efforts to improve the quality and effectiveness of the learning process. This study aims to design and develop an interactive learning model based on animation using Flash 8, which is designed to be engaging and effective for elementary school students, as well as to evaluate its impact on students’ motivation and learning outcomes. The main problem addressed is the lack of innovative and interactive learning media at the elementary level that can accommodate students’ visual and kinesthetic learning styles. This issue affects students’ enthusiasm and understanding of the concepts being taught. This research employs a Research and Development (R&D) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects are fifth-grade elementary school students, involving teachers and subject matter experts in the media development process. Data were collected through observation, interviews, questionnaires, and learning achievement tests. The development results show that the Flash 8 animation-based learning media demonstrate high levels of validity, practicality, and effectiveness. The media validity score of 4.5 out of 5 reflects strong alignment between the content, design, curriculum, and characteristics of elementary students. In terms of practicality, the media were found to be easy to use by both teachers and students during trials, with positive responses from more than 85% of participants. The media’s effectiveness is evident from the increase in students’ learning motivation, indicated by greater participation and interest in learning activities. Thus, it can be concluded that the development of Flash 8-based animation learning media holds great potential for implementation at the elementary school level as a more engaging, interactive, and effective learning tool.